Re-doing the audit - Cho, Isabel J.; Lennox, Clive; Li, Xiangyu (Journal of Accounting and Economics, 2026)
This study investigates the practice of re-audits—where an incoming audit firm re-audits the prior year’s financial statements previously examined by a predecessor audit firm. We examine the costs and benefits of such re-audits. We find that re-audits are more likely when the risks of misstatement are high and when incoming auditors can expect to win more clients by identifying material misstatements overlooked by predecessor auditors. Our results show that incoming auditors who perform re-audits are more successful in winning new clients from predecessor auditors. Moreover, re-audits result in significantly more restatements. However, consistent with the resource-intensive nature of re-audits, we also find that they are associated with longer audit delays and higher audit fees. Overall, we conclude that re-audits have important consequences for financial statement users, incoming auditors, and predecessor auditors.